Evaluation of pest management practices against sucking pests of Bt cotton - BIRAH, AJANTA; TANWAR, R K; KUMAR, ANOOP; SINGH, S P; KUMAR, RAKESH; KANWAR, V (The Indian Journal of Agricultural Sciences, 2019)
The impact of non-pesticide farmer’s practice (Jind district, Haryana) adopted by a group of farmers on pestpopulation, natural enemies and yield parameters was studied and compared with Integrated Pest Management strategyand pesticide based farmers’ practice within same villages where this group has implemented their pest managementstrategy in Bt cotton. Comparison of population per three leaves of sucking pests (average of 3 years) indicated lowestpopulation of whitefly (adult), jassid and thrips (nymph and adult) in IPM module (7.18, 3.37 and 7.17) followedby NIFP, non-insecticidal farmer’s practice (7.70, 3.48 and 7.62) and FP, farmer’s practice (9.64, 4.14 and 9.69)respectively. While studying the interaction among sucking pest and natural enemies it was interesting to note thatthe population, in both the cases, increased gradually and after attaining the peak activity there was a declining trend.Socio-economic studies also supported the above results. In present study, the mean seed cotton yield during 2015,2016, 2017 in IPM fields was 13.75, 22.45 and 17.42 q/ha, in NIFP it was 14.20, 18.10 and 13.70 as against 8.85,16.75 and 9.30 q/ha in pesticide based farmers’ practice, respectively. The incremental benefit cost ratio in IPM fieldswas 2.87, 3.56, 3.81 and it was 4.09, 3.53, 3.66 in NIFP fields as against 1.60, 1.99, 1.82 in FP during 2015, 2016and 2017, respectively. It is evident that by adopting IPM strategy, sucking pests in Bt cotton can be successfullymanaged along with conservation of natural enemies with minimum application of insecticides.